2015
DOI: 10.1016/j.drugalcdep.2015.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Cortical thinness and volume differences associated with marijuana abuse in emerging adults

Abstract: Background The prevalence of marijuana (MJ) use among youth and its legalization for medical or recreational use has intensified public health endeavors of understanding MJ effects on brain structure and function. Studies indicate that MJ use is related to impaired cognitive performance, and altered functional brain activation and chemistry in adolescents and adults, but MJ effects on brain morphology in emerging adults are less understood. Methods 15 MJ users (age 21.8±3.6, 2 females) and 15 non-using (NU) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 111 publications
(145 reference statements)
1
25
0
Order By: Relevance
“…For instance, GMVs of brain regions including the thalamus mediated the effects of early life adversities on antisocial behavior (Mackey et al, 2016). Thalamic volume was significantly smaller in marijuana users compared to non-users and associated with greater non-planning and overall impulsivity (Mashhoon et al, 2015). In patients with psychotic disorders suicidal behavior was associated with reduced GMV in cortical and subcortical structures including the left thalamus (Giakoumatos et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, GMVs of brain regions including the thalamus mediated the effects of early life adversities on antisocial behavior (Mackey et al, 2016). Thalamic volume was significantly smaller in marijuana users compared to non-users and associated with greater non-planning and overall impulsivity (Mashhoon et al, 2015). In patients with psychotic disorders suicidal behavior was associated with reduced GMV in cortical and subcortical structures including the left thalamus (Giakoumatos et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the difference in marijuana use by teens with PCE was largely driven by a greater number of males compared to girls with PCE. Given findings indicating that marijuana use among teens increases risk for psychosis (Green et al, 2016), poorer visual selective attention (Nicholls et al, 2015), lower academic achievement (Arria et al, 2015; Bechtold et al, 2016), and reduction in cortical thickness (Mashhoon et al, 2015), males with PCE could be at increased risk for negative effects of marijuana use. However, additional studies considering use quantity, frequency and/or marijuana use disorder symptoms would provide important clarifying information.…”
Section: Discussionmentioning
confidence: 99%
“…While three studies have found larger volumes of cerebellar structures in adolescent frequent cannabis users [13,21,22], three also report equivocal findings or decreases in cerebellar volumes [17,23,24]. Frequent cannabis users have also been shown to have thinner prefrontal cortex [15,25], although several studies have not replicated these findings [14,26,27]. Finally, inconsistent results are apparent in amygdala, striatum, and cingulate cortex [10,13,15], despite their high density of CB1 receptors.…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have reported associations between frequent cannabis use in adolescents and young adults and reductions in hippocampal volumes [10][11][12]. However, other studies do not replicate these reductions [13][14][15][16][17], including one longitudinal study [18]. Similarly, orbitofrontal cortex volumes have been examined, with mixed results [19,20].…”
Section: Introductionmentioning
confidence: 99%